СОЦІАЛЬНО - ЕКОНОМІЧНІ ЗМІНИ В ПОЛЬЩЕ - ВИКЛИК СИСТЕМЕ ОСВІТИ. ВИБРАНІ АСПЕКТИ СОЦІОЛОГІЇ (Педагогіка вищої та середньої школи, 2004)
The author investigates the problem of the influence of social and economic changes on the system of education in the country.